Behavioral Economics in Green Marketing: How to Push Consumers to Make Responsible Choices (Nudge Theory) - Rachynska, Halyna; Petrukha, Nina; Sereda , Nataliia; Petrukha , Serhii; Bratko , Oleksandra (International Review of Management and Marketing, 2026)
The study addresses the growing importance of corporate social responsibility and environmentally responsible consumption in the context of global environmental challenges. Traditional marketing tools are becoming less effective, increasing the need for behavioral economics instruments, particularly “nudging”, which influences consumer choices through changes in decision-making architecture without limiting freedom of choice. The research aimed to substantiate the theoretical foundations of behavioral tools in green marketing and develop practical recommendations for their business implementation. The study applied systematic analysis, synthesis, comparative analysis, abstraction, and modeling. The findings demonstrate that effective green marketing depends on psychological, social, and cultural factors influencing consumer behavior. The most efficient approaches combine green defaults, informational and social nudges, and digital behavioral tools that personalize consumer engagement. The study also highlights ethical considerations, emphasizing transparency and preservation of consumer autonomy. Practical recommendations include adapting behavioral strategies to target audiences, integrating them with traditional marketing instruments, and using digital technologies for personalized communication. The results can support businesses in strengthening customer loyalty, competitiveness, and sustainable consumption practices.